Isomorphism in russian terminology - M A Bocharova (Russian Language Studies, 2010)
The article investigates the dynamics of linguists' views on the problem of isomorphism in Russian terminology. The author considers the scientific language to be an open dynamic system whose structure is isomorphic to the structure of logical connections between scientific field notions and to serve as a sign model for this scientific field.